Aplicação de zamac-8 em molde-protótipo usinado e análise do moldado em polipropileno - Gryzinski, Ismael (2011)
The reason for the existence of a prototype mold is to obtain a quickly injected with the same material and using the same manufacturing process of the final product with low cost. Their models can serves as prototypes, pilot batches, preseries or the need to cover a lower demand for products or small batches. Criteria for manufacturability and mechanical qualities are important in the manufacture of prototype mold, but these criteria are only valid if this mold is capable of producing injected with a similar quality to the product injected into a conventional mold. However, there are few studies concerning the use of alternative material for prototype mold and the influence of that material into the product injected. Thus, the main objective of this study is to characterize a prototype mold machined in zinc alloy (Zamak-8), by analyzing the physical properties and mechanical properties of the polypropylene (PP) injected into this tool and compare it injected into the steel. The results show that the PP injected into zamac-8 has characteristics similar to the injected in steel mold, without contamination. Thus, this material can be recommended for the purpose for injection mold.